2021
DOI: 10.3390/molecules26165004
|View full text |Cite
|
Sign up to set email alerts
|

An Update on COVID-19 Vaccine Induced Thrombotic Thrombocytopenia Syndrome and Some Management Recommendations

Abstract: The thrombotic thrombocytopenia syndrome (TTS), a complication of COVID-19 vaccines, involves thrombosis (often cerebral venous sinus thrombosis) and thrombocytopenia with occasional pulmonary embolism and arterial ischemia. TTS appears to mostly affect females aged between 20 and 50 years old, with no predisposing risk factors conclusively identified so far. Cases are characterized by thrombocytopenia, higher levels of D-dimers than commonly observed in venous thromboembolic events, inexplicably low fibrinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 77 publications
(73 reference statements)
0
30
0
Order By: Relevance
“…Immune globulin prevents antibody-mediated platelet clearance and may down-regulate platelet activation by immune complexes by blocking platelet FcRγIIA receptors (127). Therefore, prompt initiation of IVIg (1g/kg over two days if needed) that is likely to influence the disease process, regardless of the severity of thrombocytopenia, and continuing to review the clinical course, is recommended for VITT (128). Contrastingly, clinicians should avoid all forms of heparin (i.e.…”
Section: Recommendations For Diagnosis and Management Of Cvst After C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Immune globulin prevents antibody-mediated platelet clearance and may down-regulate platelet activation by immune complexes by blocking platelet FcRγIIA receptors (127). Therefore, prompt initiation of IVIg (1g/kg over two days if needed) that is likely to influence the disease process, regardless of the severity of thrombocytopenia, and continuing to review the clinical course, is recommended for VITT (128). Contrastingly, clinicians should avoid all forms of heparin (i.e.…”
Section: Recommendations For Diagnosis and Management Of Cvst After C...mentioning
confidence: 99%
“…Severe bleeding and/or the need for surgical intervention may favor platelet transfusion following the initiation of IVIg, non-heparin anti-coagulation, and fibrinogen replacement if its level is less than 1.5 g/L (116,117). Platelet transfusion should be considered in life-threatening bleeding situations (128). In other words, platelet transfusion is an optional treatment to support anticoagulation, and its superiority to critical care by argatroban (low dose) without platelet transfusion has not yet been confirmed (116,117).…”
Section: Recommendations For Diagnosis and Management Of Cvst After C...mentioning
confidence: 99%
“…Mohta et al have reported 12 cases of eruptive pseudoangiomatosis, a similar vascular lesion that commonly occurs in the pediatric age group and is associated with ChAdOx1 nCoV-19 coronavirus vaccine (recombinant) in India [7]. The possible vascular injury [8,9] or immune dysregulation [10] caused by the COVID-19 vaccination could play a role in the development of these eruptive vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent Arabic reports showed that the incidence of thrombocytopenia and peculiar thrombotic events might be more common in viral vector technology based COVID-19 vaccine [ 25 , 26 ]. According to the recent management recommendation, mass COVID-19 vaccination should continue but with special caution [ 27 ].
Fig.
…”
Section: Pathophysiology Of Thrombotic Disorder and Problem In Covid-19/covid-19 Vaccinationmentioning
confidence: 99%
“…As earlier mentioned, number of cases with COVID-19/COVID-19 vaccine related thrombosis should continue if the COVID-19 pandemic still persists. Although the main exact pathogenic mechanisms are unknown, both vaccine and host factors should play important roles [ 27 ]. More case reports and studies on clinical epidemiology, clinical feature and management of the cases will be the future trend.…”
Section: Future Perspectivesmentioning
confidence: 99%